Potential of Cameroonian isolates of Beauveria bassiana and Metarhizium anisopliae for the biocontrol of the banana aphid, Pentalonia nigronervosa, vector of banana bunchy top virus - Enoh, A.C.; Akoachere, J.F.; Fossi, T.B.; Membang, G.; Ngatat, S.; Fotso Kuate, A.; Hanna, R.; Kumar, P.L.; Fiaboe, K.K.M. (2024)
Metarhizium anisopliae (Metschnikoff) Sorokin and Beauveria bassiana (Balsamo) Vuillemin are entomopathogenic fungi commonly used in microbial control of arthropods. In this study, we evaluated the insecticidal potential of six isolates of B. bassiana (BIITAC10.3.3, BIITAC6.2.2, and BIITAC8.1.5) and M. anisopliae (MIITAC11.3.4, MIITAC6.2.2, and MIITAC6.4.2) from Cameroon, against the banana aphid Pentalonia nigronervosa Coquerel, the vector of the banana bunchy top virus (BBTV). Pathogenicity tests were initially conducted using B. bassiana and M. anisopliae isolates at a concentration of 3.2 × 106 conidia/ml on P. nigronervosa adults sourced from four agroecologies in Cameroon. Four isolates (BIITAC6.2.2, BIITAC10.3.3, BIITAC8.1.5, and MIITAC6.2.2) were highly pathogenic, causing greater than 75% aphid mortality in all populations. A significant decrease in aphid fecundity was observed with BIITAC6.2.2, MIITAC6.2.2, and BIITAC10.3.3. These three isolates were in a test of a series of four fungal concentrations (3.2 × 101, 3.2 × 102, 3.2 × 104, and 3.2 × 106 conidia/ml). produced LC50 of 1.31 × 101 and 3.12 × 10−2 for BIITAC10.3.3 and MIITAC6.2.2, respectively. MIITAC6.2.2 had the lowest LC90 (1.55 × 103). Our results strongly support the continued development of biopesticides based on one or more of the three fungal entomopathogens for the control of banana aphids as a component of an Integrated Pest Management (IPM) strategy for the reduction of the prevalence and transmission of BBTV under field conditions.